Treatment of oak decline using pressurized injection capsules of antifungal materials - Fernandez-Escobar, R.; Gallego, F. J.; Benlloch, M.; Membrillo, J.; Infante, J.; de Algaba, A. Perez (European Journal of Forest Pathology, 1999)
Quercus ilex and Quercus suber trees growing at several sites in Extremadura, Western Spain, that were showing symptoms of oak decline were injected with potassium phosphonate, quinosol or carbendazim using a low-pressure method of trunk injection composed of a pressurized capsule system. A team of four people injected between 120 and 189 trees per day, depending upon the density of the undergrowth vegetation. This labour cost represented, approximately, 15–20% of the total cost of the treatment. The potassium phosphonate-injected trees showed a significant improvement in vegetative growth within 2 years of the injection treatment, and they also showed some recovery from the decline symptoms during the third year. Only one injection treatment of an average of 3.5 capsules (corresponding to 24.5 g phosphonic acid) per tree of approximately 36 cm in diameter, was necessary to reduce the disease severity significantly. Indirectly, these results corroborate the implication of Phytophthora cinnamomi in oak decline within Spanish Quercus woodlands.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Oak decline; phosphonic acid; trunk injections (PG)